2007
DOI: 10.1111/j.1745-7254.2007.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphine enhances purine nucleotide catabolism in vivo and in vitro

Abstract: Aim: To investigate the effect and mechanism of morphine on purine nucleotide catabolism. Methods: The rat model of morphine dependence and withdrawal and rat C6 glioma cells in culture were used. Concentrations of uric acid in the plasma were measured by the uricase-rap method, adenosine deaminase (ADA) and xanthine oxidase (XO) in the plasma and tissues were measured by the ADA and XO test kit. RT-PCR and RT-PCR-Southern blotting were used to examine the relative amount of ADA and XO gene transcripts in tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Significant increases in UA concentration in plasma were observed in the rats following both morphine and heroin administration. The enzymatic activities of ADA and XO were found to be enhanced significantly in the brain and other organs of rats administered heroin, and morphine was shown to increase ADA and XO gene expression in the rat brain cortex (Liu et al, 2007;Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Significant increases in UA concentration in plasma were observed in the rats following both morphine and heroin administration. The enzymatic activities of ADA and XO were found to be enhanced significantly in the brain and other organs of rats administered heroin, and morphine was shown to increase ADA and XO gene expression in the rat brain cortex (Liu et al, 2007;Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, in some organs, including the brain, purine nucleotide synthesis relies exclusively on salvage pathways. Previously, our research showed that gene expression levels of HGPRT, AK, and APRT, essential enzymes in the purine nucleotide salvage pathway, are down-regulated by heroin both in vivo and in vitro (Li et al, 2011;Liu et al, 2007). HGPRT catalyzes the salvage of the purine bases hypoxanthine and guanine to produce nucleotides (Balasubramaniam, Duley, Christodoulou, 2014).…”
Section: Mrna Transcript Levels Of Key Purine Nucleotide Metabolic Enmentioning
confidence: 99%
See 3 more Smart Citations